PENGARUH UMUR, UKURAN, DAN PROFITABILITAS PERUSAHAAN TERHADAP PERATAAN LABA - Rut Puspita Sari; Putriana Kristanti (Jurnal Riset Akuntansi dan Keuangan, 2017)
Income smoothing is one of the ways used by management to reduce fluctuations in earnings obtainedin order to profit in accordance with the desired target. This study aimed to test: the effect of firm age,firm size, and firm profitability on income smoothing on companies listed in the Indonesia StockExchange. The sample is determined based on purposive sampling, a total of 265 manufacturingcompanies during the 2010-2014 period. Technical analysis of the data using logistic regression. Theresults showed that the age of the firm, firm size, and profitability influence the practice of incomesmoothing.Keywords: Firm Age, Firm Size, Firm Profitability, Income Smoothing